Life is an Adventure: From Action Theory to Action - Peg Brand Weiser (University of Kansas Libraries, 2021)
Myles Brand was the fourth President of the National Collegiate Athletic Association (NCAA). This essay tracks the progression of Brand's early work in action theory, his theoretical turn to the moral role of education, and finally his legacy of principled leadership on issues of ethics and social justice within intercollegiate athletics during what I refer to as "The Brand Era." I show that Brand's writings and speeches from 1970 through 2002 offer a foundation for the conceptual strategies employed in meeting NCAA challenges from 2003 through 2009. His innovative conceptualization of the applied philosophy of sport moved him forward from action theory into action.